Antibiotic Prophylaxis in Caesarean Section - Thapa, Raj Kumar; Bhandari, Bishrawa; Adhikari, Kapil; Katila, Pramila; Baral, Prativa; Khan, Gulam Muhammad (Intelektual Pustaka Media Utama, 2012)
To study the use of prophylactic antibiotics in caesarean section (CS), a cross-sectional study was conducted at Western Regional Hospital of Nepal for 3 months period. Non-random purposive sampling was done and data about the women undergoing CS was collected using the data collection form. This study included a total of 188 women undergoing CS. The result showed that 42.6% of the women were of 20-24 years of age followed by 31.9% of 25-29 years. The indications for CS included cephalopelvic disproportion (62.2%), oligohydraminos (20.2%), breech presentation (18.1%) and fetal distress (10.1%). Failed induction, multiple pregnancy, failure to progress, dystocia and preeclampsia/eclampsia were relatively rare indications. Elective and emergency CS was common between the age group20-24 and 25-29 years whereas emergency CS was more common than elective in the age group below 20 and above 39 years. In 99.5% cases metronidazole, 50.5% cases ciprofloxacin and 50.5% cases gentamycin was used for prophylaxis. Of the total women 50% of the women got 3 antibiotics for prophylaxis followed by 47.9% of them who got 2 antibiotics for prophylaxis. The average length of hospital stay was found to be 6.7 days. The results obtained from the study revealed that CS was prevalent in Western region of Nepal and prophylactic antibiotics were commonly used in women undergoing CS. Key Words: Caesarean section, Antibiotic prophylaxis, NepalDOI: http://dx.doi.org/10.11591/ijphs.v1i1.280